Edukasi Penyalahgunaan Psikotropika Bagi Remaja Di Desa Pulo Kecamatan Tempaeh Kabupaten Lumajang - Khoiron Badrul Aini; Didik Iswahyudi; Suparno Suparno (International Forum of Researchers and Lecturers, 2023)
The spread of psychotropics is starting to become widespread among teenagers, the abuse of psychotropics is an action that is not permitted both from a health and legal perspective. This research aims to find out how widespread psychotropic abuse is in Pulo village and how efforts are made to prevent psychotropic abuse. This research uses a qualitative approach and an interactive qualitative research type. The data collection techniques used were observation, interviews and documentation. Based on research on psychotropic abuse education for teenagers in Pulo village, the distribution of psychotropic pills type Y is widespread and often abused, from teenagers to the elderly. The distribution of these pills can come from friends in the school environment, home environment and work environment. In order to create a healthy environment and free from psychotropic abuse. They should hold positive activities that involve village youth, such as more sporting and religious events, and regularly provide education or socialization about the dangers and ongoing impacts of psychotropic abuse.